ANALYSIS OF THE EFFECT OF QUALITY, PRICE, INFRASTRUCTURE ON TOURIST SATISFACTION AND INTEREST IN RAJA AMPAT, SOUTHWEST PAPUA - Supriatna, Intan Iriani; Rachmadhani, Mirga Maulana; Gani, Mardhiah; Ahistasari, Asih; Wahyudien, Mohammad Arief Nur; Maricar, Abdul Razak (Journal of Industrial Engineering Management, 2024)
Success industry tourism is greatly influenced by quality services , prices , and infrastructure . Urgency study This based on Quality services that include accommodation , food , transportation and guides tourism , which affects satisfaction and loyalty tourists . Price as factor important in decision tourists , where prices are appropriate with quality service increase mark perception destination ; and infrastructure like transportation , accommodation and facilities general , which plays a role in comfort security tourists . Research objectives For analyze influence quality , price and infrastructure to satisfaction and interest Tourists Return to Raja Ampat. Research Methods use method quantitative with analysis statistics descriptive with SPSS software . The results of analysis influence There are 2 variables that are significant and have influence that is quality service and satisfaction traveler to interest traveler return to Raja Ampat, 2 variables that are not significant and not own influence that is prices and infrastructure to interest traveler return to Raja Ampat.